Letter (copy) : Roberto Vega Gonzalez - Citrine, Walter 1887-1983
012b-0009-001 International. WMC/WJB/AT/14. 12th September, 1939. Sr. F.P. Cruz, Federación de Sindicatos de Trabajadoras al Servicio del Estado, Lucerna 55 - Primer Piso, Mexico, D.F. Dear Sir, We duly received your letter dated the 12th August and were very sorry to learn of the danger to which Comrade Gonzalez is exposed for his action on behalf of the Spanish workers. A similar request was received by us with regard to Comrade Vega. We are in communication with the appropriate authorities and you can rely upon our doing all we can to induce the Tribunals in Spain to exercise clemency in dealing with their case. Yours faithfully, General Secretary. see 910/416 292/946/12b/9